Zagreb indices of block-edge transformation graphs and their complements - Bommanahal Basavanagoud; Shreekant Patil (Indonesian Journal of Combinatorics, 2017)
In this paper, we obtain expressions for first and second Zagreb indices and coindices of block-edge transformation graphs G^{ab}. Analogous expressions are obtained also for the complements of G^{ab}.